PENGARUH PERENDAMAN JENIS BUAH TERHADAP PENURUNAN KADAR KADMIUM (Cd) PADA UDANG VANNAME (Litopenaeus vannamei) TAMBAK INTENSIF DEKAT DAN JAUH MANGROVE - Anggraini, Bella; Sulistyani, Widya Sartika; Widowati, *Hening (BIOLOVA, 2021)
Vanname shrimp (Litopenaeusvannamei) has filter feeder properties that can filter all the food contained in the sediment. Cd is a type of metal that will settle in the sediment. Cd can accumulate in the shrimp body and endanger human health if consumed. The objectives of study were 1) to determine the effect of immersion of fruits on the reduction of Cd levels, 2) to determine which types of fruits were more appropriate to reduce Cd levels in Vanname Shrimp in remote and intensive ponds. near mangroves and 3) to make posters as learning media for class X high school on environmental pollution. The research was conducted using the CRBD method (completely randomized block design) and analyzed with a one-way anova test to determine the effect of fruits on the reduction of Cd levels. The research was conducted in April 2020 in Pasir Sakti, East Lampung and analyzed at the Chemical Analytical Laboratory of the Muhammadiyah University of Malang. The results showed that soaking vanname shrimp using fruits had the effect of reducing Cd levels in shrimp meat. The type of fruits that gave the best reduction effect was Citrus aurantiifolia which was able to reduce the Cd to 270.87 ppb or decreased by 46.28% for intensive pond shrimp near mangroves, and able to reduce the Cd to 521.4 ppb or decreased by 44.62% for intensive mangroves distant pond. This research produces learning resources in the form of posters that are suitable for use in class X high school biology learning environmental pollution material.